(untitled) (Islamic Sciences Journal, 2023)
This research deals with the Christian religion, what are its most important features, and the places where the Christian identity is defined. It has three topics: I explained in the first topic: the definition of the Christian religion, and its most prominent prophets, and there are two requirements: the first requirement: the definition of the Christian religion in language and terminology: and the second requirement: the most prominent prophets of religion The Christian: Then, in the second topic, I showed: the characteristics of the Christian religion, doctrinal, legal, and ethical, and it contains four demands: The first requirement: religious identity in the sources of teachings of the Christian religion: The second requirement: religious identity in Christian sanctities, and the third requirement: the religious gap in worship and practical rulings Christianity and the fourth requirement: Christian religious identity in holidays and holy days.